LESSON STUDY IN EFL PRACTICES: TEACHERS’ ANXIETY AND FACTORS INFLUENCING IT - Istikharoh, Lutfi (J-ELLiT (Journal of English Language, Literature, and Teaching), 2021)
Abstract: This study was a part of Lesson Study program which focused on developing and maintaining English interaction in EFL classes. This paper presents the teachers’ anxiety and the factors contributing in which English is used as a medium of instruction in English classes. Two teachers who were enrolled in a public school of  Purwokerto, participated in this study. The subjects’ anxiety was investigated using interview and classroom observation. The result provided evidence that the subjects had experienced anxiety when they used English to their students in certain conditions. The research findings showed that there were four factors causing anxiey among teachers when they used English in the classroom: 1) class preparation; 2) students and classroom profile; 3) self-confidence; and 4) physical condition. On a whole, teachers’ anxiety deals with both technical and academic matters. Keywords: EFL Classes, English as a Medium of Instruction, Teacher’s anxiousness